The association between prenatal atrioventricular septal defects and chromosomal abnormalities - Morlando, M; Bhide, A; Familiari, A; Khalil, A; Morales-Roselló, J; Papageorghiou, A; Carvalho, J (Elsevier, 2016)
Objectives Atrioventricular septal defect is associated with a high risk of a chromosomal abnormality, particularly trisomy 21. The aim of this study is to assess the rate of trisomy 21 in fetuses diagnosed with an atrioventricular septal defect and to examine the influence of prior screening on the rate of trisomy 21. Methods Electronic ultrasound database was searched to identify fetuses diagnoses with an atrioventricular septal defect from 2002 to 2014. Rate of trisomy 21 and other aneuploidies was calculated among fetuses with normal situs. The prevalence of trisomy 21 and other aneuploidies was assessed in women with low and high first trimester risk for trisomy 21, using a cut-off value of 1:150 and 1:250. Results total 110 fetuses with a diagnosis of atrioventricular septal defect were identified. Among the 98 fetuses with normal situs, the prevalence of trisomy 21 was 46% (95% CI: 36–56%). Using a 1:150 threshold, the rate of trisomy 21 within the low-risk group was 41% (95% CI: 27–57%) while in the high-risk group it was 70% (95% CI: 52–83%), significantly higher than in the low risk group (p = 0.028). Similar results were obtained when the 1:250 threshold was applied (66% versus 41%, p = 0.055). Conclusions The rate of trisomy 21 among fetuses identified with an atrioventricular septal defect in the second trimester is high even in those that undergo first trimester combined screening. Some fetuses with a high-risk screening result show a normal karyotype. Therefore, an offer of an invasive procedure to check fetal karyotyping is indicated. Knowledge of these rates may be helpful for parents in the decision making process.